Üretim ve Kalkınma Ekonomisi Sorunları ve Yönetimi - Özen, Sadettin; Gürsev, Samet (İstanbul Kültür Üniversitesi / İktisadi ve İdari Bilimler Fakültesi / İktisat Bölümü, 2014)
The basic problem of the developing production economics is to estimate the balance of demand and supply, the priorities in sectors and product capacities, and also investment capitals. In the developing process it is important the visions and long term planning decision criteria, the medium term planning decision criteria because of the using productivity investment capitals. The solutions of these problems are to increase the importance of the average costs and also investments with added values. These problems are to increase the importance of the social perceptions and responsibilities depending on benefits. So, this study has focused the investigating optimum and economic solutions of the priorities in sectors and product capacities, and also investment capitals in sectors. The study has researched the as the maximizing the productivity, the economic and social benefits. In the same way, this study’s goal is to bring out analyzing the productivity problems depending on the developing production economics models. So the developing production economics concepts are tried to be defined accordance with the views of the realism, empiricism, pragmatism and rationalism.
Keywords: Üretim; teknoloji ve kalkınma ekonomisi; marjinal ve ortalama verimlilik; karlılık; stratejik çözümleme ve planlama; Production economics; productivity; visions; long term planning; decision criteria; demand; sectors and product capacities; investment capitals